EXPERIMENTAL EVALUATION OF L-AMINO ACID AS CHEMICAL AGENT FOR ENHANCED OIL RECOVERY - ATTA, DENNIS YAW (2021)
Surfactant flooding is one of the most attractive methods of Enhanced oil recovery (EOR). Most conventional surfactants are environmentally unfriendly and expensive, with some unstable at either higher salinity and or temperature condition. The natural amino acid (AAs) presents a wide range of bio-friendly, cheap chemicals and can be stable at higher reservoir conditions. However, the influence of AAs (L-arginine, L-lysine-HCl, L-methionine, L-tyrosine and L-tryptophan) on oil recovery is yet to be understood. Factors such as the stability of AAs at high temperature and salinity, interfacial tension (IFT) reduction potential, wettability alteration ability, the adsorption capacity and the potential recovery factor will give an understanding of their EOR applicability. This thesis reports on the experimental evaluation of AAs as EOR chemicals.